With Consolo's 'voices' (Prassi Ecdotiche della Modernità Letteraria, 2017)
The aesthetic and cognitive quality of the works of Vincenzo Consolo had benn askig for longtime an edition able to give it a stable presence in the canon of the great authors of the 20th century. On the other hand, the characteristics of Consolo's texts, with their well-known linguistic but also generally cultural complexity, asked the editor to modulate the apparatus so as to offer the reader the tools for an easier understanding. The systematic investigation in Consolo's Archivea has made it possible to face up to all the difficulties presented by the edition, achieving significant results both in terms of documentation and in terms of critical interpretation.
Keywords: Vincenzo Consolo; complete work; author's will; editor